PERAN PENTAHELIX DALAM PENGEMBANGAN DESA WISATA SUMBERBULU, KECAMATAN MOJOGEDANG, KABUPATEN KARANGANYAR - Chandra, Teddy (Jurnal Pariwisata Budaya: Jurnal Ilmiah Pariwisata Agama dan Budaya, 2025)
Pentahelix is ​​a form of collaboration and cooperation that involves five main strength elements in a development program. The five main elements consist of academia, business, government, community and mass media. With this synergy, it is hoped that development programs in the tourism sector will be able to be optimized in order to achieve sustainable tourism development goals. This study aims to find an overview of the role of the pentahelix in tourism development in the Sumberbulu tourist village, Karanganyar Regency. The research method used is qualitative research. Data collection techniques were carried out by means of literature studies, observations and interviews. The results of the study indicate that four of the five pentahelix elements have played a role and contributed to the development of the Sumberbulu tourism village. The four elements are academics, government, society and the mass media. Only business elements that have not been involved.